The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.healthplace.2008.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood walkability and its particular importance for adults with a preference for passive transport

Abstract: a b s t r a c tIn this study, differences in physical activity between adults living in high versus low walkable neighbourhoods were examined. In Sint-Niklaas, Belgium, neighbourhood walkability was defined by geographical map data and observations. One high walkable and one low walkable neighbourhood were selected. A sample of 120 adults between 20 and 65 years old, agreed to participate in the study and wore a pedometer for seven days. Self-reported physical activity and psychosocial data were collected. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
96
3
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 36 publications
7
96
3
6
Order By: Relevance
“…This result is opposite to the results found for adults in international and Belgian studies (Sallis and Owen, 2002;De Bourdeaudhuij et al, 2003, Van Dyck et al, 2009, showing consistently that adults living in a high-walkable neighbourhood are more physically active.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This result is opposite to the results found for adults in international and Belgian studies (Sallis and Owen, 2002;De Bourdeaudhuij et al, 2003, Van Dyck et al, 2009, showing consistently that adults living in a high-walkable neighbourhood are more physically active.…”
Section: Discussioncontrasting
confidence: 94%
“…Because of the indistinctness in the current literature on adolescents and the clear link between walkability and PA in adults in the United States (Sallis and Owen, 2002), Australia and Europe (De Bourdeaudhuij et al, 2003;Van Dyck et al, 2009), the main aim of the present study was to investigate whether this association also exists in adolescents. Therefore, we hypothesized that adolescents living in a high-walkable town centre are more physically active than adolescents living in a less-walkable suburb.…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the mean step counts found in two other Belgian studies. 25,31 The present study also has some limitations. First, no Geographic Information Systems database was used to collect objective data on the physical environmental attributes in the different neighborhoods.…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, the present results are very similar to our previous study, where the interactions between transport-related psychosocial factors and the physical environment (urban versus suburban) were examined in relation to physical activity. 25 Results of that study showed that only in the suburban neighborhood, did adults with a high intention and a preference for active transport take more steps than those with a low intention and a preference for passive transport. In the urban neighborhood, no differences in step counts were found according to personal factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation